IDENTIFIKASI DAMPAK SEBARAN DEBU VULKANIK TERHADAP PENERBANGAN DI BANDAR UDARA I GUSTI NGURAH RAI (STUDI KASUS: ERUPSI GUNUNG AGUNG PERIODE OKTOBER SAMPAI DESEMBER 2017 - Winarni, Oktiana; Tjahyo Baskoro, Winardi; Sumaja, Kadek (SATUKATA: Jurnal Sains, Teknik, dan Studi Kemasyarakatan, 2023)
Mount Agung is one of the active mountains in the Bali region which is in the north of Bali and is about 75 kilometers from I Gusti Ngurah Rai Airport which is in the southwest of Mount Agung. Mount Agung has an eruption record from early October to late December 2017 with Level 3 to Level 4. By using 4 methods, namely Himawari-8 satellite imagery, trajectory and dispersion hysplit and Streamline models, a pattern of volcanic ash distribution was produced that directed towards the South to Southwest due to the influence of wind patterns and cyclones with wind speeds reaching 10 to 100 knots at altitudes of 400, 500, 600, 700 and 850 hPa and the minimum particle concentration value in volcanic ash eruption of Mount Agung reaches 〖3,8〗^(-21) mass/m³ and the maximum particle concentration value reaches 〖1,0〗^(-11) mass/m³. In addition, the distribution of volcanic ash leading to I Gusti Ngurah Rai Airport also has an impact on the safety of flight activities both during take-off and landing, so that on November 27 to 30, 2017 I Gusti Ngurah Rai Airport was officially closed and canceled flights to and from Bali.